Evolutionary Systems Biology 2021
DOI: 10.1007/978-3-030-71737-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Complex Biological Systems: Tackling the Parameter Curse Through Evolution

Abstract: As we all know: "Nothing in biology makes sense except in the light of evolution" (Dobzhansky [9]). Among the challenges of modeling complex biological systems is to determine the relevant parameters. Common practice is to extract parameters from the literature, or to determine them from ongoing experiments, or by collectively fitting the parameters to the experimental results the model tries to explain. Doing so ignores, or at least does not exploit, Dobzhansky's wisdom. In this perspective paper we argue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…We found that 148 out of 218 HHP networks satisfied this condition (the parameter values are shown in S1 Data ). This consistency between evolutionary-determined and stable parameter values has been suggested previously to support the reliability of sustainable conditions [ 34 ].…”
Section: Resultssupporting
confidence: 81%
“…We found that 148 out of 218 HHP networks satisfied this condition (the parameter values are shown in S1 Data ). This consistency between evolutionary-determined and stable parameter values has been suggested previously to support the reliability of sustainable conditions [ 34 ].…”
Section: Resultssupporting
confidence: 81%